CD4+CD25+CD127-Foxp3+ and CD8+CD28- Tregs in Renal Transplant Recipients: Phenotypic Patterns, Association With Immunosuppressive Drugs, and Interaction With Effector CD8+ T Cells and CD19+IL-10+ Bregs - Aly, Mostafa G.; Ibrahim, Eman H.; Karakizlis, Hristos; Weimer, Rolf; Opelz, Gerhard; Morath, Christian; Zeier, Martin; Ekpoom, Naruemol; Daniel, Volker (Frontiers in Immunology, 2021)
Introduction Gaps still exist regarding knowledge on regulatory cells in transplant recipients. We studied the phenotypic patterns of CD4+, CD8+CD28- Tregs, and CD19+IL-10+ Bregs in the blood of healthy controls (HC), end-stage kidney disease patients (ESKD), early and late stable renal transplant recipients (Tx), and transplant recipients with steroid-treated acute cellular rejection 1 week–3 months after successful treatment. We also investigated the relationship between immunosuppressive drugs and the aforementioned regulatory cells in transplant recipients. Methods We recruited 32 HC, 83 ESKD, 51 early Tx, 95 late Tx, and 9 transplant patients with a recent steroid-treated acute cellular rejection. Besides CD19+IL-10+ Bregs, we analyzed absolute and relative frequencies of CD4+CD25+CD127-Foxp3+ Tregs and CD8+CD28- Tregs and their expression of IL-10, TGF-ß, IFN-g, and Helios. Results We found a negative correlation between absolute CD4+CD25+CD127-Foxp3+ Treg and relative CD19+IL-10+ Breg frequencies in early Tx recipients (r=-0.433, p=0.015, n=31). In that group, absolute CD4+CD25+CD127-Foxp3+ Tregs were negatively associated with steroid dose and tacrolimus trough levels (r=-0.377, p = 0.021, n=37; r=-0.43, p=0.033, n=25, respectively), opposite to IL-10+ Bregs, whose frequency apparently was not negatively affected by potent immunosuppression early posttransplant. We found also lower CD4+CD25+CD127-Foxp3+ Tregs in patients treated with basiliximab or rATG as compared with ESKD patients (p=0.001 and p <0.001, respectively). No difference in absolute IL-10+ Bregs could be detected among these 3 patient groups. Early Tx recipients showed lower CD4+CD25+CD127-Foxp3+ Tregs within 3 months of antibody induction than after 3 months (p = 0.034), whereas IL-10+ Bregs showed higher relative counts during the first 3 months post antibody induction than after 3 months (p = 0.022). Our findings suggest that IL-10+ Bregs decrease with time posttransplantation independent of the effect of antibody induction and dose of other immunosuppressive drugs. Conclusion These findings suggest that CD19+IL-10+ Bregs and CD4+CD25+CD127-Foxp3+ Tregs behave in opposite ways during the early posttransplant period, possibly due to a predominant negative impact of high doses of immunosuppressants on Tregs. CD19+IL-10+Bregs do not seem to be suppressed by antibody induction and early potent immunosuppression with chemical drugs.